Efektivitas Pelayanan Digital Program Samsat Keliling Di Kota Mataram - Muhammad Ali; M Awaluddin; Abdul Salam (Universitas Muhammadiyah Mataram, 2019)
The effectiveness of the digital SAMSAT mobile service program is a success in improving the welfare of its members and the community in general with the aim of research to determine the effectiveness of digital services on the SAMSAT mobile program in the city of Mataram and what are the supporting factors and obstacles the city of Mataram. The method used in this study is descriptive qualitative method with data collection techniques, namely interviews, observation, literature study, and documentation. Data analysis in qualitative research, carried out at the time of data collection takes place, namely reduction data, display data, and draw conclusions. The results of this study are the effectiveness of the mobile SAMSAT digital service program in the city of Mataram. So far the services carried out by mobile SAMSAT have been effective. the number that has paid PKB as many as 7.507 vehicles and the amount of money as much as Rp. 3,542,442,111. while SAMSAT mobile 2 operates in the cakra and gebang sub-district offices, the number of which has paid PKB is 2,382 vehicles and the amount of money is Rp. 1,236,041,341. the last being SAMSAT mobile 3 which operates in the sindu market and the udayana roundabout, the number of those who have paid PKB is 2,538 vehicles and the amount of money is Rp. 913,443,402. and those who paid PKB in 2018, traveling around SAMSAT 1 in Sangkareang Park and Mayure Village Office, the number of those who had paid PKB was 10,522 vehicles and the amount of money was Rp. 6,627,326,321. while SAMSAT around 2 operates in the cakra and gebang sub-district offices, the number of which has paid PKB as much as 6,603 vehicles and Rp. 3,708,124,026. the last being SAMSAT mobile 3 which operates in the sindu market and the udayana roundabout, the number of which has paid PKB as many as 3,617 vehicles and the amount of money as much as Rp. 2,740,330,200. judging from the increase in the number of people who have paid PKB from 2017-2018, according to the scale of the assessment made, it can be concluded that the effectiveness of digital services on the SAMSAT mobile program in the city of Mataram has been effective.